Relationship between body temperature, weight, and hematological parameters of black tufted‐ear marmosets (Callithrix penicillata). Issue 3 (12th April 2016) - Pereira, Lucas Cardoso; Barros, Marilia
Abstract: Background: Basal thermal values of captive adult black tufted‐ear marmosets ( Callithrix penicillata ) in a thermoneutral environment were measured via different methods, along with body weight and hematological parameters. Method: Body temperatures were recorded with rectal (RC), subcutaneous (SC) microchip transponder and infrared (left and right) tympanic membrane (TM) thermometries. Thermal values were correlated with body mass and some hematological data. Results and conclusions: Similar RC and SC temperatures were observed, these being significantly higher than the left and right TM values. SC temperature was positively correlated and in close agreement with RC measurements. Although body temperatures were not influenced by gender, capture time, or body weight, they were correlated with hematological parameters. Thus, body temperatures in this species seem to reflect some of the characteristics of the assessments' location, with SC microchip transponders being a less invasive method to assess body temperature in these small‐bodied non‐human primates.